Synthesis of intermediate derivatives from Schweinfurthin G using chiral ionic liquid - Nguyen Thuy Linh; Bui Thi Minh Anh; Tran Van Hieu; Phi Thi Dao; Tran Thu Huong; Doan Thi Mai Huong; Pham Van Cuong (Vietnam Journal of Science and Technology, 2023)
Schweinfurthins possess a wide diversity of important biological and pharmacological activities. To date, more than fifty schweinfurthins and their analogues have been prepared for the investigation of structure-function relationships. Schweinfurthin G, one of the most representative of schweinfurthins containing the hexahydroxanthene moiety, was found to strongly inhibit the growth of cancer cell lines when evaluated on the U87 cell line (EC50 of 0.04 µM), and on the KB cell line (IC50 of 0.06 µM). Ionic liquids have been regarded as “solvents of the future” and applied in various fields. They have been utilized most widely in modern organic synthesis as an environmentally friendly alternative to conventional organic solvents and catalysts due to their flexible, nonvolatile, noncorrosive, low viscous properties and they still maintain similar and sometimes enhanced chemical selectivity and reactivity of organic reactions. In this paper, we present the synthesis of intermediate compounds 2 and 3, which are the key compounds for synthesizing the derivatives of schweinfurthin G using chiral ionic liquid. These compounds are the key blocks to further synthesize schweinfurthin G derivatives for biological activity tests.